Effects of niacin and aspirin on serum prolactin and body temperature of heifers fed endophyte-infected tall fescue - Robert L. Larson; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1992)
Feeding niacin to cattle consuming endophyte (Acremonium coenophialum)-infected tall fescue elevated their serum prolactin concentrations to levels similar to those of heifers fed hay containing a low content of endophyte. Heifers fed high-endophyte hay, with or without aspirin, had lower serum prolactin concentrations than heifers fed low-endophyte fescue hay (P<.1). Compared to control cattle fed high-endophyte hay, neither niacin nor aspirin lowered morning or evening body temperatures during the period August 16 to September 4. Feeding aspirin did not lower body temperature or increase prolactin concentration in animals fed high-endophyte fescue forage. Some benefit was seen when niacin was added to the diet, as evidenced by higher (P<.01) prolactin concentrations; however body temperature was not lowered.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Fescue; Niacin; Aspirin; Prolactin; Body temperature